2001
DOI: 10.1046/j.1365-2842.2001.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the pyramidal process of the palatine bone in relation to implant placement in the posterior maxilla

Abstract: The placement of dental implants in the molar region of the maxilla is often difficult because of insufficient bone volume and the inferior bone quality. In order to avoid these limitations, the pillar of bone, which is composed of the maxillary tuberosity, the pyramidal process of the palatine bone and the pterygoid process of the sphenoid bone, was introduced for implant placement. In fact, the pyramidal process is the posterior structure where implants are placed but until now, there is no available data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 10 publications
2
26
0
4
Order By: Relevance
“…It subsequently proceeds upwards between both wings of the pterygoid processes and finds its encroachment in the pterygoid or scaphoid fossa of the sphenoid bone 21,43 . The pyramidal and pterygoid processes are composed of dense cortical bone and the average thickness of bone at their juncture is 6-6.7 mm 21,25 . If an implant is passed through this juncture at an angle of 45 degrees, it can incorporate up to 8-9 mm of dense cortical bone and its apex protrudes 2 mm into the pterygoid fossa 21 .…”
mentioning
confidence: 99%
“…It subsequently proceeds upwards between both wings of the pterygoid processes and finds its encroachment in the pterygoid or scaphoid fossa of the sphenoid bone 21,43 . The pyramidal and pterygoid processes are composed of dense cortical bone and the average thickness of bone at their juncture is 6-6.7 mm 21,25 . If an implant is passed through this juncture at an angle of 45 degrees, it can incorporate up to 8-9 mm of dense cortical bone and its apex protrudes 2 mm into the pterygoid fossa 21 .…”
mentioning
confidence: 99%
“…Twenty full-texts were excluded for the following reasons: clinical case studies, 22,[28][29][30]36,40,41 biomechanical study, 42 orthodontic study, 43,44 data not localized, 45 morphometric study, 46 in vitro study, 47 anatomical and radiological study, 35,48 and implants not placed in the region of the tuberosity or missing data. [49][50][51][52][53] Since there are few studies addressing the topic, relevant excluded clinical studies are summarized in Table 2.…”
Section: General Outcomesmentioning
confidence: 99%
“…20,21,[23][24][25][26][32][33][34][35] A systematic review indicated a 92% survival rate (first year) for implants placed in the pterygoid region 20 ; however, evidence-based reviews addressing implants placed in the tuberosity region are scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If the height, length, and/or width of the tuberosity are not adequate, however, the implant can be angled and the apex made to engage either the pterygoid process, the pyramidal plate of the palatine bone, or both. Recent observations and measurement of the height, anteroposterior distance, and mediolateral distance of the pyramidal process indicate that placement of implants in the lower half of the pyramidal process is advantageous (36).…”
Section: Tuberosity and Pterygoid Implantsmentioning
confidence: 99%